Maria Antônia: uma rua e seus significados - Silva, Fernando Santos da (2018)
This paper proposes to approach the perceptions that we developed when analyzing the urban space called "street", where we experience many of our experiences and we establish most of our relations, be they political, economic, social and cultural. Such experiences occur daily in this stage of events, either by their spatiality or even by their temporality, giving rise to interpretations and reinterpretations of the observed reality, its meanings and its connections. For this approach, the concepts of "perception" of Maurice Merleau-Ponty, of "place of memory" of Pierre Nora were used and, in relation to the valorization of the street as a space of sociability and visibility of the urban territory, separately by urban planners Kevin Lynch and Jane Jacobs. As a physical object of study was chosen Maria Antônia Street, in Consolação neighborhood, due to the fact that this place has unique characteristics in the urban and cultural geography of São Paulo since it began to appear on the maps of the Capital. It was observed that its various meanings raised by memory, by observation and by the social imaginary succeed and alternate in the axis of time, passing through the episodes of 1968 known as "Maria Antonia's War", and culminating with the current configuration, marked by a singular experiential, social and cultural plasticity. Through the launching of this new look on Maria Antonia Street, it is intended to contribute to the perception that this São Paulo public road has specific attributes and meanings, both diversified and complex, that have not been treated in a more complete way, by the corresponding historiography.